2005
DOI: 10.1124/jpet.105.094383
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activity and Inverse Agonism at the M2Muscarinic Acetylcholine Receptor

Abstract: Introduction of a single-point mutation (Asn to Tyr) at position 410 at the junction between transmembrane domain 6 and the third extracellular loop of the human M 2 muscarinic acetylcholine (mACh) receptor generated a mutant receptor (N410Y) that possesses many of the hallmark features of a constitutively active mutant receptor. These included enhanced agonist binding affinity and potency, in addition to agonist-independent accumulation of [ 3 H]inositol phosphates in cells coexpressing the chimeric G␣ qi5 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The similarity between the two estimates shows that the atropine-rescued hM 1AA430 -431 receptor exhibits stability comparable with that of the wild-type hM 1 receptor, and that the effect of atropine cannot be attributed to prevention of receptor internalization and degradation. The hM 1AA430 -431 mutant behaves differently from M 2 and M 3 muscarinic receptors bearing a N6.58Y mutation that causes internalization and constitutive activation in an atropinereversible manner (Dowling et al, 2006;Nelson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity between the two estimates shows that the atropine-rescued hM 1AA430 -431 receptor exhibits stability comparable with that of the wild-type hM 1 receptor, and that the effect of atropine cannot be attributed to prevention of receptor internalization and degradation. The hM 1AA430 -431 mutant behaves differently from M 2 and M 3 muscarinic receptors bearing a N6.58Y mutation that causes internalization and constitutive activation in an atropinereversible manner (Dowling et al, 2006;Nelson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in the Introduction, the position corresponding to amino acid 514 in the human M 3 -AChR was shown to generate constitutive activity in all muscarinic receptor subtypes (Dowling et al, 2006;Nelson et al, 2006). In particular, the mutation N514Y was reported to cause constitutive activity in the M 3 -AChR and was analyzed in detail (Dowling et al, 2006).…”
Section: Muscarinic M 3 Receptor Kinetics 241mentioning
confidence: 99%
“…Several different mutations have been demonstrated to cause constitutive receptor activity for the muscarinic acetylcholine receptor family (Spalding and Burstein, 2006). In particular, the amino acid in position 6.58 [according to the Ballesteros/ Weinstein numbering scheme (Ballesteros and Weinstein, 1995)] at the interface of transmembrane domain (TM) 6 and the extracellular loop was shown to cause constitutive activity in all five muscarinic AChR subtypes (Spalding et al, 1997;Ford et al, 2002;Dowling et al, 2006;Nelson et al, 2006), whereas alternative mutations in the E/DRY motif in TM3 or in the NPXXY motif in TM7 close to the cytoplasmic side (Spalding and Burstein, 2006;Smit et al, 2007) did not cause constitutive activity at the M 1 -AChR. This particular position corresponds to amino acid 514 in the human M 3 -AChR, and the mutation N514Y within the human M 3 -AChR has been thoroughly characterized for its effects on basal receptor activity, agonist affinity, and inverse agonist effects (Dowling et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies may be due to unique interactions of atropine with the receptor. While commonly described as an antagonist, atropine also exhibits properties of an inverse agonist [39,40] . For example, previous research found that continuous treatment with atropine can lead to an increase in receptor expression [23,29] .…”
Section: Discussionmentioning
confidence: 99%